Pemeriksaan Kesehatan Gratis sebagai Upaya Promotif dan Preventif Penyakit Tidak Menular melalui Kolaborasi Lintas Sektor, Sleman, Yogyakarta - Rizky Triutami Sukarno; Azizah Nurlitasari Tambulana; Henny Cloridina; Uttie Nooring Fivaprilani; Adlina Karimina Nurul Husna; Suci Harini; Sekar Sari Arum Palupi; Aji Bagus Widyantara; Astika Cahyarani; Nasya Kamila Tsania Mas'udi; Syafiya Rahma Aqila (FKM UIN Sumatera Utara Medan, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes, and obesity represent a significant public health burden in Indonesia, including the Special Region of Yogyakarta. To enhance early detection and preventive action, the Faculty of Medicine, Universitas ‘Aisyiyah Yogyakarta, in collaboration with the Sleman District Health Office through Puskesmas Gamping 2, conducted a Free Health Check-up on Sunday, October 12, 2025, from 08.00 to 12.00 WIB at the Siti Bariyah Building, Faculty of Medicine UNISA Yogyakarta. This community service employed a Participatory Action Research approach, engaging participants throughout the process from registration, anthropometric measurements, vital signs assessment, simple laboratory tests, and visual acuity checks, to medical consultation, personalized health education, symptomatic medication, and referral for at-risk individuals. Among 141 participants, the majority were young adults (20-29 years) and female; 33.3% were classified as obese, 44.0% as pre-hypertensive, 7.1% as pre-diabetic, and 60.3% had abnormal cholesterol levels. The intervention facilitated early identification of NCD risk, immediate preventive measures, and referral to health services for high-risk participants. The program also strengthened the framework for sustainable community-based screening, provided practical experience for medical students, and established a replicable model of promotive and preventive collaboration between academic institutions and local health authorities. The results demonstrate that structured community interventions combining screening, education, and follow-up can effectively contribute to NCD prevention and support long-term public health initiatives.